The Strategic Role of the Da'i Nagari in Driving Rural Development in Pasaman, West Sumatra - Syafriani, Desi; Ridho, Muhammad; Kamal, Muhiddinur (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This paper analyzes the strategic role of Da'i Nagari (local preacher) as Da'i assisting the nagari (village) government in driving rural development in Pasaman Regency, West Sumatra. Da'i Nagari is a local government-created program that rewards preachers in West Sumatra. This study aims to describe the significant role of Da'i Nagari in the development process. This research is critical since Da'i Nagari is a specific regional government initiative that only exists in West Sumatra. By providing an overview of the presence of Da'i Nagari in Pasaman Barat, this qualitative descriptive study elucidates the role of Da'i Nagari in the development process. Additionally, this study addresses academic concerns regarding the potential positive effects of the Da'i Nagari program on rural development. The results of this study are revealed by describing Da'i Nagari as an extension of the regional government in developing rural communities. The presence of Da'i Nagari assists the community in resolving various religious problems, including character building, religious information development, and social issues.